Use of waste glass fines to improve rigidity ratio of asphalt - D. E. Ewa; J. O. Ukpata; G. A. Akeke; A. A. Etika; E. I. Adah (Cogent Engineering, 2022)
Management of waste glass is a huge environmental challenge in Nigeria and most developing countries. This study evaluates the influence of using Waste Glass Fines (WGF) as an asphalt filler to improve the Rigidity Ratio (RR) of asphaltic concrete. As stand-alone fillers in hot asphalt mixtures, the performances of quarry dust and waste glass powder were compared. The effect of waste glass as a partial replacement for quarry dust on the rigidity ratio of asphalt mixtures was then assessed using the Marshall Stability method. An optimum bitumen content (OBC) of 5.0% was established for the control specimens. Quarry dust (QD) was partially replaced with Waste Glass Fines (WGF) at 5% to 100% replacement levels. Results showed that while stability, Flow, and VMA at 5% OBC were found to satisfy the minimum requirement of typical Marshal Design Criteria for QD and WGF fillers, and Air Voids and VFB did not meet minimum specification. For QD+WGF samples, an optimum WGF content of 10% was found to give satisfactory results for both binders and wearing courses. The air voids were reduced, while VFB increased. The resistance of the mix against permanent deformations measured by the rigidity ratio or Marshal Quotient at this optimum WGF was 1.49KN/m2. This value is higher than those at 100% QD (1.33kN/m2) and 100% WGF (0.84kN/m2), Increased MQ values indicated a stiffer mix capable of spreading the applied load and resisting creep deformation. This indicates that Waste Glass Fines can improve asphalt resistance to permanent deformations.